From Craft to Profession: The Evolution of Archival Education and Theory in North America - Schaeffer, Roy (Archivaria, 1994)
There has been much discussion on the true nature of archivally relevant knowledge. Sixty years of debate has centred on whether the proper preparation of the archivist lies in historical study or exposure to the broad field of information science. As with all aspiring professions, there has also been uncertainty as to whether the archivist can or should be educated in a graduate university environment or trained through traditional on-the-job apprenticeship. Only recently have North American archivists and their educators begun to examine the intellectual basis of their work, to explore the full range of the archival body of knowledge and its possible connections to other fields of study. In their struggle toward true professional status, archivists must recognize the essential nature of academic research and theory construction to the development of a unique and vital archival culture. RÉSUMÉ La nature réelle du savoir archivistique a suscité de longs débats. Pendant près de soixante ans on s'est interrogé à savoir si les études historiques ou l'initiation au vaste champ des sciences de l'information constituait la meilleure formation pour l'archiviste. Comme pour toutes les carrières en voie de professionnalisation, il y a eu une certaine ambivalence concernant la pertinence d'encadrer l'archiviste dans un programme de second cycle universitaire ou de lui assurer un apprentissage traditionnel en le formant sur le tas dans son milieu de travail. Ce n'est que récemment que les archivistes nord-américains et leurs professeurs ont commencé à évaluer les fondements intellectuels de leur travail et à explorer l'éventail de l'ensemble du savoir archivistique et ses raccordements possibles avec les autres champs d'étude. Dans leur lutte pour la reconnaissance de leur statut professionnel, les archivistes se doivent de reconnaître l'importance fondamentale de la recherche académique et de l'élaboration des théories dans le développement d'une culture archivistique fondamentale et unique.